Carcass characteristics, meat quality, and fatty acid composition of wild-living mallards (Anas platyrhynchos L.) - Janiszewski, P; Murawska, D; Hanzal, V; Gesek, M; Michalik, D; Zawacka, M (Poultry science, 2018)
The aim of this study was to determine the carcass characteristics, meat quality, and fatty acid composition of wild-living mallards. The experimental materials comprised 30 mallards (1:1 sex ratio) harvested during the hunting season in northeastern Poland. The carcasses were transported to the laboratory where they were weighed individually, plucked, dressed, and dissected. The proximate chemical composition and physicochemical properties of meat and the fatty acid profile of breast muscle lipids were determined, and a histological analysis was performed. Body weight (BW) and carcass weight were higher in males than in females (P ≤ 0.05), whereas the percentage share of carcass tissue components was similar in both sexes. Edible components accounted for approximately 60% (♂) to 60.7% (♀) of the total BW of mallards, including lean meat; 40.9% (♂) to 41.5% (♀), skin with subcutaneous fat; 10.7% (♂) to 10.8% (♀), and giblets; 8.3% (♂) to 8.4% (♀). Breast muscles had high protein content (23.51%♀ to 23.6% ♂) and low fat content (0.82% ♂ to 0.84% ♀). In the fatty acid profile of breast muscle lipids, saturated fatty acids (SFA) accounted for 39.1% (♂) to 39.04% (♀), monounsaturated fatty acids (MUFA)-for 17.31% (♂) to 17.33% (♀) and polyunsaturated fatty acids (PUFA)-for 43.61% (♀) to 43.64% (♂). The diameters of type IIA and type IIB muscle fibers were lower in males than in females (P ≤ 0.05), whereas lipid storage sites in muscles were similar in both sexes. The values of cooking loss (CL), water-holding capacity (WHC), pH24, and color parameters of breast meat were comparable in males and females. The results of this study indicate that wild-living mallards, both males and females, are characterized by high meat quality, and that seasonal mallard harvests can provide meat with desirable eating attributes, attractive to consumers.
Keywords: Poland; carcass characteristics; Animals, Wild; meat quality; maso; Fatty Acids; mužské pohlaví; Polsko; divoká zvířata; ženské pohlaví; zvířata; mallard; Meat; kachny; Ducks; mastné kyseliny; muscle fibers; Female; fatty acids; Male; Animals